Fresh cocoa pod husk as an ingredient in the diets of growing pigs - E. O. K. Oddoye; S. W. A. Rhule; K. Agyente-Badu; V. Anchirinah; F. Owusu Ansah (African Journal of Pig Farming, 2017)
The growth rate, feed intake, feed to gain ratio and cost of gain of growing pigs fed diets containing 250 g kg-1 dry cocoa pod husk (control) (diet I) and 200 (diet II) or 300 (diet III) g kg-1 cocoa pod husk in the form of fresh (wet) cocoa pod husk were investigated in a feeding trial set up as a completely randomized design, at two (2) locations, with three (3) treatments replicated four (4) times and lasting 140 days. The variances at the two locations proved to be homogenous and as such data from the two (2) locations was pooled with the analysis being handled as a singlefactor design with treatment as the only factor. There was no significant difference (p > 0.05) between treatments for average daily weight gain, average daily feed intake and feed conversion ratio. Cost of gain for 300 g kg-1 fresh (wet) cocoa pod husk treatment was, however, significantly higher (p < 0.05) than the other feeds. It was concluded that feeding fresh (wet) cocoa pod husk to growing pigs, up to 300 g kg-1 (on air-dry weight basis) of the diet had no deleterious effects on the pigs